Freemium economics : leveraging analytics and user segmentation to drive revenue - Seufert, Eric Benjamin (Savvy manager's guides., 2014)
Freemium Economics presents a practical, instructive approach to successfully implementing the freemium model into your software products by building analytics into product design from the earliest stages of development. Your freemium product generates vast volumes of data, but using that data to maximize conversion, boost retention, and deliver revenue can be challenging if you don't fully understand the impact that small changes can have on revenue. In this book, author Eric Seufert provides clear guidelines for using data and analytics through all stages of development to optimize your implementation of the freemium model. Freemium Economics de-mystifies the freemium model through an exploration of its core, data-oriented tenets, so that you can apply it methodically rather than hoping that conversion and revenue will naturally follow product launch. By reading Freemium Economics, you will: Learn how to apply data science and big data principles in freemium product design and development to maximize conversion, boost retention, and deliver revenue Gain a broad introduction to the conceptual economic pillars of freemium and a complete understanding of the unique approaches needed to acquire users and convert them from free to paying customers Get practical tips and analytical guidance to successfully implement the freemium model Understand the metrics and infrastructure required to measure the success of a freemium product and improve it post-launch Includes a detailed explanation of the lifetime customer value (LCV) calculation and step-by-step instructions for implementing key performance indicators in a simple, universally-accessible tool like Excel.